The Effectiveness of Galore Group Learning Model to Improve Students’ Writing Ability at The Fourth Semester of Makassar Muhammadiyah University - Amaliah, Nur (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2018)
The problem statement of this research is to know the effectivenes Galore Group effective to improve the students’ writing ability at the fourth semester of Makassar Muhammadiyah University. This research applied True-experimental design with the pre-test post-test control group design. The researcher applied the purposive sampling technique in choosing the sample of the research which consisted of 60 people (class E and F). The implementation of Galore Group Learning Model was effective in improving writing ability of the fourth year students of Makassar Muhammadiyah University. It was proved by the ttest (7,90) which higher than t-table (2.02).